Degradable biological membrane and preparation method thereof
By combining the modification treatment of microcrystalline cellulose with PBAT and PLA, the existing PBAT has been solved in the lack of mechanical properties and lack of breathable and waterproofing functions, and a degradable biofilm with excellent mechanical properties and breathable and waterproofing functions has been prepared. , meets the needs of the packaging field.
Patent Information
- Application Number
- CN202411287324.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing biodegradable plastic PBAT has problems with immature production processes and insufficient mechanical properties, especially in the packaging field, where the demand for materials with excellent mechanical properties and breathable and waterproof functions has not been effectively met.
By carboxylation, crosslinking and graft modification of microcrystalline cellulose and combined with PBAT and PLA, a degradable biofilm with excellent mechanical properties and breathable and waterproofing function was prepared. The method includes dispersing microcrystalline cellulose in a citric acid solution for hydrolysis, adding aluminum hydroxide and monohydroxy terminated silicone oil to form modified particles, followed by mixing with PBAT and PLA in a twin screw extruder and casting Bidirectional stretching to form a film with waterproof and breathable function.
It realizes the dual functions of improving the mechanical properties of the degradable biofilm and breathable and waterproofing, ensuring the wide application prospects of materials in packaging and other fields.
Smart Images

Figure BDA0005043463160000081
Abstract
Description
Technical field:
[0001] The invention relates to the field of degradable plastics, and more particularly to a degradable biofilm and a preparation method thereof. Background technology:
[0002] With the advancement of modern science and technology, the application areas of plastic products are constantly expanding, and "white pollution" has become a global problem that needs to be solved. Against this background, degradable polymer materials have become a hot topic of research at home and abroad.
[0003] Polybutylene adipate / terephthalate (PBAT) is a copolyester synthesized from aliphatic dibasic acid, aromatic dibasic acid and butanediol. As a new type of biodegradable material, it has broad application prospects. However, the current production process of PBAT is still immature, and the market price is 2-3 times that of ordinary plastics. In addition, the defects of PBAT's mechanical properties (such as low tensile strength) also limit its commercial use. Blending modification is the most commonly used method in plastic modification, so PBAT can be blended with low-priced, high-strength substances to improve its comprehensive performance and reduce costs.
[0004] In the research of PBAT blending, the blending materials usually selected have some defects. Cellulose has unique properties, such as low density, high toughness and strength, and biodegradability. However, cellulose also has certain defects, mainly because it is a polyhydroxy compound with certain water absorption. If it is directly blended with hydrophobic polyester, incompatibility will occur. In addition, in the fields of daily agricultural film, ground film, disposable medical protective clothing, sanitary drug packaging, food packaging, etc., both biodegradability and durability are required.
[0005] Patent CN114456359A discloses a tear-resistant and puncture-resistant PBAT copolyester material, in which adipic acid, 1.4-butanediol, terephthalic acid, propylene glycol, and tetrabutyl titanate are blended, and successively undergo two-step esterification and polycondensation to obtain PBAT-GL-0.6 copolyester; then, citric acid and microcrystalline cellulose are added for the third step of esterification to obtain a tear-resistant and puncture-resistant PBAT copolyester material. However, this solution requires the preparation of a specific PBAT copolyester, which is costly.
[0006] CN113527847A discloses a degradable breathing film, wherein anisotropic inorganic fillers are added to PLA / PBAT, and during the process of blowing a polymer masterbatch containing rod-shaped or sheet-shaped nanofillers into a film, the film is stretched in the appropriate transverse and longitudinal directions to produce micropores and a three-dimensional pore network, thereby improving the air permeability of the film. However, this solution is only applicable to methods such as blow molding.
[0007] Therefore, the preparation of a degradable biofilm with excellent mechanical properties, breathability and waterproofness has broad application prospects in packaging and other fields. Summary of the invention:
[0008] The present invention intends to provide a degradable biofilm and a preparation method thereof. The material has excellent mechanical properties and controllable biodegradability.
[0009] The present invention obtains modified microcrystalline cellulose by performing modification steps such as carboxylation, crosslinking and grafting on microcrystalline cellulose, thereby preparing a degradable biofilm of PBAT / PLA / modified microcrystalline cellulose. The film has excellent mechanical properties and air permeability and waterproof functions.
[0010] To achieve the technical purpose of the present invention, the present invention provides a degradable biofilm, which is made of the following raw materials in parts by weight: 60-70 parts of PBAT, 30-40 parts of PLA, 5-10 parts of microcrystalline cellulose composite modified particles, 0.5-2 parts of chain extender, 1-2 parts of coupling agent, 0.5-1 parts of anti-hydrolysis agent, and 0.5-1 parts of antioxidant.
[0011] Furthermore, the chain extender is styrene-methyl methacrylate-glycidyl methacrylate copolymer.
[0012] Furthermore, the coupling agent is one or more of a silane coupling agent, an aluminate coupling agent, and an aluminum-titanium composite coupling agent.
[0013] Furthermore, the anti-hydrolysis agent is a carbodiimide anti-hydrolysis agent.
[0014] Further, the antioxidant is one or more of antioxidant 1010 , antioxidant 168 , antioxidant 1076 or antioxidant 1790 .
[0015] Furthermore, the preparation method of the microcrystalline cellulose composite modified particles is as follows: disperse the microcrystalline cellulose in a citric acid solution, use hydrochloric acid as a catalyst, and perform a hydrolysis reaction at 50-90°C for 2-6 hours; the resulting reaction suspension is repeatedly washed with distilled water until it is neutral; the suspension is treated in an ultrasonic cell disruptor for 0.5-1 hour to obtain a carboxylated microcrystalline cellulose aqueous solution, aluminum hydroxide and monohydroxy-terminated silicone oil are added successively for modification to form a gel, and after aging at room temperature for 12-24 hours, it is dried at 80-100°C to constant weight, and ground to obtain microcrystalline cellulose composite modified particles.
[0016] The material-liquid ratio of the microcrystalline cellulose to the citric acid solution is between 1:20 and 1:40; the concentration of the citric acid solution is between 2-4 mol / L; the concentration of the hydrochloric acid solution is between 5-6 mol / L; and the amount of the hydrochloric acid solution accounts for 1-5% of the citric acid solution.
[0017] The amount of aluminum hydroxide used accounts for 1-3% of the mass of microcrystalline cellulose, the amount of monohydroxyl-terminated silicone oil used accounts for 0.5-2% of the mass of microcrystalline cellulose, and the average molecular weight is 1000-2000 g / mol.
[0018] The method for preparing the degradable biofilm comprises the following steps:
[0019] (1) 60-70 parts of PBAT, 30-40 parts of PLA, 3-10 parts of microcrystalline cellulose composite modified particles, 0.5-2 parts of chain extender, 1-2 parts of coupling agent, 0.5-1 parts of anti-hydrolysis agent, and 0.5-1 parts of antioxidant are mixed and stirred in a mixer, and then added into a twin-screw extruder for extrusion, cold air cooling, and granulation to obtain a masterbatch of PBAT / PLA / modified microcrystalline cellulose;
[0020] (2) adding the masterbatch prepared in step (1) into a casting machine for casting, and obtaining a sheet after cooling;
[0021] (3) biaxially stretching the sheet obtained in step (2) and then heat-setting it to obtain a PBAT / PLA / modified microcrystalline cellulose film.
[0022] Furthermore, the temperature of the mixer in step (1) is 80-110° C., and the rotation speed is 800-1200 r / min.
[0023] Furthermore, in step (1), the extrusion temperatures of zones 1 to 6 of the twin-screw extruder are 110, 120, 130, 130, 120, and 120° C., respectively, and the die head temperature is 120° C.
[0024] Furthermore, in step (2), the casting temperature is 180-200°C, and the cooling temperature is 20-30°C.
[0025] Furthermore, the biaxial stretching in step (3) includes: first longitudinal stretching and then transverse stretching, wherein the temperature of the longitudinal stretching is 95-105°C, the stretching ratio is 3-4, the temperature of the transverse stretching is 100-110°C, the stretching ratio is 3-5, and the temperature of the heat setting is 110-115°C.
[0026] The present invention performs carboxyl modification on microcrystalline cellulose, and uses the generated carboxyl groups to crosslink with aluminum hydroxide to form composite particles with a certain crosslinking network, and adds monohydroxyl-terminated silicone oil to give the composite particles better hydrophobicity, which can ensure that the modified microcrystalline cellulose can be better dispersed in the polymer. At the same time, the introduction of monohydroxyl-terminated silicone oil, while further enhancing the hydrophobicity and dispersibility, will lead to the presence of long chains with a certain degree of freedom in the system, which can improve the moisture permeability of the overall material.
[0027] For carboxyl modification, the carboxyl content in microcrystalline cellulose should not be too high. When the carboxyl content is too high, the internal cross-linked network of microcrystalline cellulose will be too dense, which will make the dispersion effect of modified microcrystalline cellulose and PBAT / PLA polymer system worse, increase the tendency of phase separation, and finally lead to the decline of mechanical properties.
[0028] The modified microcrystalline cellulose in the present invention can be used as a nucleating agent in the system. At the same time, when the film is biaxially stretched, interface micropores are formed when the film is stretched, so that the air permeability of the film in the present invention is further enhanced.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention modifies microcrystalline cellulose by carboxylation, crosslinking and grafting, thereby improving the dispersibility of microcrystalline cellulose and PBAT / PLA polymer system; at the same time, the water contact angle of the film of the present invention is above 90°, and the moisture permeability is 130 g / m 2 / 24h or more, indicating that it has the dual functions of waterproof and breathable.
[0031] (2) The present invention controls the degree of carboxylation of microcrystalline cellulose to ensure that the internal cross-linked network of microcrystalline cellulose is maintained at an appropriate density, thereby maintaining the dispersibility of the modified microcrystalline cellulose and the PBAT / PLA polymer system, thereby ensuring the mechanical properties of the degradable biofilm.
[0032] (3) The present invention utilizes the nucleating agent effect of modified microcrystalline cellulose and further increases the air permeability of the film by biaxial stretching. Specific implementation method:
[0033] In order to make the purpose, technical scheme and advantages of the present invention more clear, the technical scheme of the present invention is further described below through specific implementation methods. Those skilled in the art should know that the embodiments are only to help understand the technical content and technical effects of the present invention and should not be regarded as limiting the present invention.
[0034] PBAT and PLA in the examples of the present invention and the comparative examples were purchased from Guangdong Jinfa Technology Co., Ltd., microcrystalline cellulose was purchased from Qufu Tianli Pharmaceutical Excipients Co., Ltd., the chain extender was KL-E4370B styrene-methyl methacrylate-glycidyl methacrylate copolymer, and other additives were all common commercially available products.
[0035] The present invention includes 4 embodiments and 3 comparative examples.
[0036] Embodiment 1:
[0037] Preparation of microcrystalline cellulose modified composite particles:
[0038] 3 parts by mass of microcrystalline cellulose are dispersed in a citric acid (3 mol / L) solution with a solid-liquid ratio of 1:20, and hydrochloric acid (6 mol / L) accounting for 5% of the volume of the citric acid solution is added as a catalyst, and stirred for hydrolysis reaction, and the hydrolysis reaction is carried out at 80°C for 3 hours; the obtained reaction suspension is repeatedly washed with distilled water until neutral; the suspension is treated in an ultrasonic cell disruptor for 0.5 hours to obtain a carboxylated microcrystalline cellulose aqueous solution, and 0.06 parts by mass of aluminum hydroxide and 0.03 parts by mass of monohydroxy-terminated silicone oil are added successively for modification to form a gel, which is aged at room temperature for 24 hours, dried at 80°C to constant weight, and ground to obtain microcrystalline cellulose composite modified particles.
[0039] Preparation method of degradable biofilm:
[0040] (1) 70 parts of PBAT, 30 parts of PLA, 5 parts of microcrystalline cellulose composite modified particles, 2 parts of chain extender KL-E4370B, 1 part of silane coupling agent KH-550, 1 part of anti-hydrolysis agent Bio-SW, and 0.5 parts of antioxidant 1010 were mixed and stirred uniformly in a mixer at 90° C. and a speed of 1000 r / min, and then added to a twin-screw extruder for extrusion, cold air cooling, and granulation, wherein the extrusion temperatures of the first to sixth zones of the twin-screw extruder were 110, 120, 130, 130, 120, and 120° C., respectively, and the head temperature was 120° C., to obtain a masterbatch of PBAT / PLA / modified microcrystalline cellulose;
[0041] (2) adding the masterbatch prepared in step (1) into a casting machine and casting at 180° C., and cooling at 20° C. to obtain a sheet;
[0042] (3) The sheet obtained in step (2) is first longitudinally stretched and then transversely stretched, wherein the longitudinal stretching temperature is 95° C. and the stretching ratio is 3, the transverse stretching temperature is 105° C. and the stretching ratio is 4, and then heat-set at 110° C. to obtain a PBAT / PLA / modified microcrystalline cellulose film.
[0043] Embodiment 2:
[0044] Preparation of microcrystalline cellulose modified composite particles:
[0045] 3 parts by mass of microcrystalline cellulose are dispersed in a citric acid (3 mol / L) solution with a solid-liquid ratio of 1:30, and hydrochloric acid (6 mol / L) accounting for 5% of the volume of the citric acid solution is added as a catalyst, and stirred for hydrolysis, and the hydrolysis reaction is carried out at 90°C for 2.5 hours; the obtained reaction suspension is repeatedly washed with distilled water until it is neutral; the suspension is treated in an ultrasonic cell disruptor for 0.5 hours to obtain a carboxylated microcrystalline cellulose aqueous solution, and 0.06 parts by mass of aluminum hydroxide and 0.05 parts by mass of monohydroxy-terminated silicone oil are added successively for modification to form a gel, which is aged at room temperature for 24 hours, dried at 90°C to constant weight, and ground to obtain microcrystalline cellulose composite modified particles.
[0046] Preparation method of degradable biofilm:
[0047] (1) 70 parts of PBAT, 35 parts of PLA, 8 parts of microcrystalline cellulose composite modified particles, 1 part of chain extender KL-E4370B, 1.5 parts of aluminate coupling agent DL411, 1 part of anti-hydrolysis agent Bio-SW500, and 1680.5 parts of antioxidant were mixed and stirred in a mixer at 90° C. and a speed of 1000 r / min, and then added to a twin-screw extruder for extrusion, cold air cooling, and granulation, wherein the extrusion temperatures of the first to sixth zones of the twin-screw extruder were 110, 120, 130, 130, 120, and 120° C., respectively, and the head temperature was 120° C., to obtain a masterbatch of PBAT / PLA / modified microcrystalline cellulose;
[0048] (2) adding the masterbatch prepared in step (1) into a casting machine and casting at 180° C., and cooling at 20° C. to obtain a sheet;
[0049] (3) The sheet obtained in step (2) is first longitudinally stretched and then transversely stretched, wherein the longitudinal stretching temperature is 100° C. and the stretching ratio is 4, and the transverse stretching temperature is 100° C. and the stretching ratio is 5, and then heat-set at 110° C. to obtain a PBAT / PLA / modified microcrystalline cellulose film.
[0050] Embodiment 3:
[0051] Example 3 uses the microcrystalline cellulose composite modified particles prepared in Example 1.
[0052] Preparation of degradable biofilm:
[0053] (1) 60 parts of PBAT, 30 parts of PLA, 8 parts of microcrystalline cellulose composite modified particles, 2 parts of chain extender KL-E4370B, 1.5 parts of aluminate coupling agent DL411, 1 part of anti-hydrolysis agent Bio-SW100, and 0.5 parts of antioxidant 1010 were mixed and stirred uniformly in a mixer at 90° C. and a speed of 1000 r / min, and then added to a twin-screw extruder for extrusion, cold air cooling, and granulation, wherein the extrusion temperatures of the first to sixth zones of the twin-screw extruder were 110, 120, 130, 130, 120, and 120° C., respectively, and the head temperature was 120° C., to obtain a masterbatch of PBAT / PLA / modified microcrystalline cellulose;
[0054] (2) adding the masterbatch prepared in step (1) into a casting machine and casting at 180° C., and cooling at 20° C. to obtain a sheet;
[0055] (3) The sheet obtained in step (2) is first longitudinally stretched and then transversely stretched, wherein the longitudinal stretching temperature is 90° C. and the stretching ratio is 3, the transverse stretching temperature is 100° C. and the stretching ratio is 4, and then heat-set at 110° C. to obtain a PBAT / PLA / modified microcrystalline cellulose film.
[0056] Comparative Example 1:
[0057] The difference from Example 1 is that the solid-liquid ratio of microcrystalline cellulose to citric acid is 1:50.
[0058] Comparative Example 2:
[0059] The difference from Example 1 is that no monohydroxy-terminated silicone oil is added.
[0060] Comparative Example 3:
[0061] The difference from Example 3 is that the amount of the composite modified microcrystalline cellulose particles used is 2 parts by mass.
[0062] The above standard specimens are tested for various properties using the following standard methods:
[0063] Mechanical properties test: The tensile strength and elongation at break of the PBAT nanocomposite film samples in the manufacturing example were tested according to the standard GB / T1040.3-2006. The film was cut into (10mm×160mm) specification samples, the clamp spacing was 40mm, the tensile speed was 200mm / min, the test was repeated 5 times, and the average value was taken to obtain the tensile strength and elongation at break.
[0064] Waterproof performance (water contact angle) test: Use a contact angle meter to test. Place the sample horizontally on the contact angle meter platform, inject distilled water onto the sample surface through a microinjection, and observe the change in contact angle. The test range is 0 to 180°.
[0065] Moisture permeability test: Use a moisture permeability tester to test. Before the test, place the sample in an environment with a temperature of 25°C and a relative humidity of 50% for 4 hours according to the provisions of GB / T26253-2010. Test conditions: temperature 25°C, relative humidity 90%, atmospheric pressure, test time 4 hours.
[0066] The test results of mechanical properties, moisture permeability and waterproof properties are shown in Table 1.
[0067]
[0068] From the results of Examples 1-3 and Comparative Examples 1-3, the present invention modifies the microcrystalline cellulose by carboxylation, cross-linking and monohydroxyl-terminated grafting, and controls the degree of carboxylation of the microcrystalline cellulose and performs biaxial stretching operations, so that the obtained degradable biofilm has good mechanical properties and waterproof and breathable functions.
[0069] From the comparison between the embodiment and comparative example 1, when the degree of carboxylation of microcrystalline cellulose is too high, the internal cross-linked network of the microcrystalline cellulose will be too dense, which will make the dispersion effect of the modified microcrystalline cellulose and the PBAT / PLA polymer system worse, and will affect the mechanical properties and air permeability of the final product.
[0070] From the comparison between the embodiment and comparative example 2, when the monohydroxy-terminated silicone oil is not added, although the mechanical properties are not affected, the waterproof and breathable properties of the film are affected due to the lack of hydrophobic groups with freedom.
[0071] From the comparison between the embodiment and comparative example 3, when the amount of modified microcrystalline cellulose is reduced, it will seriously affect the number of interface micropores formed when stretched, and ultimately have an adverse effect on the air permeability.
[0072] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A degradable biofilm, It is characterized in that The invention is prepared from the following raw materials in parts by weight: 60-70 parts of PBAT, 30-40 parts of PLA, 5-10 parts of microcrystalline cellulose composite modified particles, 0.5-2 parts of chain extender, 1-2 parts of coupling agent, 0.5-1 parts of anti-hydrolysis agent, and 0.5-1 parts of antioxidant; The preparation method of the microcrystalline cellulose composite modified particles is as follows: disperse the microcrystalline cellulose in a citric acid solution, use hydrochloric acid as a catalyst, and perform a hydrolysis reaction at 50-90°C for 2-6 hours; repeatedly wash the obtained reaction suspension with distilled water until it is neutral; treat the suspension in an ultrasonic cell disruptor for 0.5-1 hour to obtain a carboxylated microcrystalline cellulose aqueous solution, add aluminum hydroxide and monohydroxy-terminated silicone oil in succession to modify it to form a gel, age it at room temperature for 12-24 hours, dry it at 80-100°C to constant weight, and grind it to obtain the microcrystalline cellulose composite modified particles.
2. The degradable biofilm according to claim 1, It is characterized in that The anti-hydrolysis agent is a carbodiimide anti-hydrolysis agent; the chain extender is a styrene-methyl methacrylate-glycidyl methacrylate copolymer; the coupling agent is one or more of a silane coupling agent, an aluminate coupling agent, and an aluminum-titanium composite coupling agent; and the antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 1076, or antioxidant 1790.
3. The degradable biofilm according to claim 1, It is characterized in that In the preparation process of microcrystalline cellulose composite modified particles, the material-liquid ratio of microcrystalline cellulose to citric acid solution is between 1:20 and 1:40; the concentration of citric acid solution is between 2-4 mol / L; the concentration of hydrochloric acid solution is between 5-6 mol / L; and the amount of hydrochloric acid solution used accounts for 1-5% of the citric acid solution.
4. The degradable biofilm according to claim 1, It is characterized in that In the preparation process of the composite modified microcrystalline cellulose particles, the amount of aluminum hydroxide used accounts for 1-3% of the mass of the microcrystalline cellulose; the amount of monohydroxyl-terminated silicone oil used accounts for 0.5-2% of the mass of the microcrystalline cellulose, and the average molecular weight is 1000-2000g / mol.
5. The method for preparing the degradable biofilm according to any one of claims 1 to 4, Features: The steps include: (1) 60-70 parts of PBAT, 30-40 parts of PLA, 3-10 parts of microcrystalline cellulose composite modified particles, 0.5-2 parts of chain extender, 1-2 parts of coupling agent, 0.5-1 parts of anti-hydrolysis agent, and 0.5-1 parts of antioxidant are mixed and stirred in a mixer, and then added into a twin-screw extruder for extrusion, cold air cooling, and granulation to obtain a masterbatch of PBAT / PLA / modified microcrystalline cellulose; (2) adding the masterbatch prepared in step (1) into a casting machine for casting, and obtaining a sheet after cooling; (3) biaxially stretching the sheet obtained in step (2) and then heat-setting it to obtain a PBAT / PLA / modified microcrystalline cellulose film.
6. The method according to claim 5, It is characterized in that The temperature of the mixer in step (1) is 80-110° C., and the rotation speed is 800-1200 r / min.
7. The method according to claim 5, It is characterized in that In step (1), the extrusion temperatures of zones 1 to 6 of the twin-screw extruder are 110, 120, 130, 130, 120, and 120° C., respectively, and the die head temperature is 120° C.
8. The method according to claim 5, It is characterized in that In step (2), the casting temperature is 180-200°C, and the cooling temperature is 20-30°C.
9. The method according to claim 5, It is characterized in that The biaxial stretching in step (3) includes: first longitudinal stretching and then transverse stretching, wherein the longitudinal stretching temperature is 95-105°C and the stretching ratio is 3-4, the transverse stretching temperature is 100-110°C and the stretching ratio is 3-5, and the heat setting temperature is 110-115°C.
Citation Information
Patent Citations
Cellulose polyester composite material and preparation method thereof
CN112063141A
Natural polymer conductive aerogel and preparation method thereof
CN114373566A
Special full-biodegradable mulching film for garlic and preparation method thereof
CN117447849A
Cheese stick convenient to store at normal temperature and preparation method thereof
CN118415244A
Biodegradable aqueous dispersion composition and preparation method therefor
WO2023234669A1
Cited By
Degradable food packaging bag and preparation method thereof
CN120209524A
Degradable food packaging bag and preparation method thereof
CN120209524B
